(untitled) (In situ, 2025)
As part of the planned activities of the project Undersea Neolithic sites in the Croatian Adriatic (IP-2022-10-3893, project leader: M. Parica), there was an underwater archaeological research and field survey in the seabed of the islet of Galešnjak near the settlement of Turanj. The research leader, who carried out the research in mid-November, was Mate Parica (University of Zadar), and the deputy research leader was Mladen Pešić (International Center for Underwater Archaeology – Zadar). The research focused on the survey of the Neolithic communication embankment and the trial trenching of the seabed north of Galešnjak.